State Accountability for Corporate Climate Offenses : International and Developing Country Legal Perspectives - Putra, Rian Rusmana; Kaloko, Ilhamda Fattah; Harmain, Irfan; Dahlan; Prakarsa, Taruna (Melayunesia Law, 2025)
This study examines state legal responsibility in addressing corporate- driven climate violations in developing countries, focusing on the gap between normative commitments and actual enforcement. The central question is how state liability should be constructed to effectively regulate corporations that contribute significantly to greenhouse gas emissions and environmental degradation. Using a juridical normative and comparative approach, the analysis covers Indonesia, Brazil, and South Africa to identify similarities, differences, and weaknesses in integrating international principles into domestic legal systems. The findings reveal that while national laws recognize the duty to protect the environment and uphold human rights, enforcement remains fragmented, symbolic, and subordinated to short-term economic interests. This creates a structural accountability gap that facilitates corporate impunity, compounded by power imbalances, inadequate institutional capacity, and the absence of robust extraterritorial enforcement mechanisms. The novelty of this research lies in an integrated framework combining state responsibility, corporate accountability, and climate justice, emphasizing extraterritorial obligations and independent national climate adjudication mechanisms. This model operationalizes climate justice as a binding legal standard, harmonizes domestic laws with international obligations, and improves access to justice for affected communities. The tangible output of this study is a normative–comparative regulatory model and policy recommendations for legislators, environmental law practitioners, and international organizations to reform legal frameworks for corporate climate accountability in developing countries. By bridging the gap between norms and practice, the framework offers both conceptual contributions and practical guidance for legal reform, ultimately promoting sustainable development grounded in ecological protection and intergenerational equity.